5(x-2)-3=-5(-2x+3)-9

Simple and best practice solution for 5(x-2)-3=-5(-2x+3)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)-3=-5(-2x+3)-9 equation:



5(x-2)-3=-5(-2x+3)-9
We move all terms to the left:
5(x-2)-3-(-5(-2x+3)-9)=0
We multiply parentheses
5x-(-5(-2x+3)-9)-10-3=0
We calculate terms in parentheses: -(-5(-2x+3)-9), so:
-5(-2x+3)-9
We multiply parentheses
10x-15-9
We add all the numbers together, and all the variables
10x-24
Back to the equation:
-(10x-24)
We add all the numbers together, and all the variables
5x-(10x-24)-13=0
We get rid of parentheses
5x-10x+24-13=0
We add all the numbers together, and all the variables
-5x+11=0
We move all terms containing x to the left, all other terms to the right
-5x=-11
x=-11/-5
x=2+1/5

See similar equations:

| -10.3=w/7+7.2 | | 5m=20+3m | | (40+x)36+(92−(40+x))⋅48=C | | 4*(2x+7)=16 | | -h-20=12h+19 | | 50+14x=330 | | 15–5(4x–7)=50 | | 8(x)=110-3(x) | | 6/8x4+2=6 | | 16=10–3m | | 3(4x+9)=-25+4 | | 37=7r-5 | | 8(x-1)=568 | | (40+x)36+(92−(40+x))⋅48=C | | 18-5(x-10)=-7 | | 8x5=5x | | 39−5d=–56 | | 17=7+2p | | x+10x3=x5 | | 5x-6=14+1x | | f/2+11=14 | | 5(3+x)=17 | | 6(5m-3)=1/2(24+12) | | -9y-47=4(y-2) | | 4n+13=3(1+2n) | | x-1/2(8-x)=x+3(4x)-x | | -45=3(1+4x) | | 5x+9+2x=65 | | 9w+20+6w=15w-8 | | y+4/5=81/3 | | 2x-7-4x=-1 | | 1.5x-0.666666667x=2 |

Equations solver categories